Socioeconomic Resilience : Multi-Hazard Estimates in 117 Countries - Hallegatte, Stephane; Bangalore, Mook; Vogt-Schilb, Adrien (World Bank, Washington, DC, 2016)
This paper presents a model to assess the socioeconomic resilience to natural disasters of an economy, defined as its capacity to mitigate the impact of disaster-related asset losses on welfare. The paper proposes a tool to help decision makers identify the most promising policy options to reduce welfare losses from natural disasters. Applied to riverine and storm surge floods, earthquakes, windstorms, and tsunamis in 117 countries, the model provides estimates of country-level socioeconomic resilience. Because hazards disproportionally affect poor people, each $1 of global natural disaster-related asset loss is equivalent to a $1.6 reduction in the affected country’s national income, on average. The model also assesses policy levers to reduce welfare losses in each country. It shows that considering asset losses is insufficient to assess disaster risk management policies. The same reduction in asset losses results in different welfare gains depending on who (especially poor or nonpoor households) benefits. And some policies, such as adaptive social protection, do not reduce asset losses, but still reduce welfare losses. Post-disaster transfers bring an estimated benefit of at least $1.30 per dollar disbursed in the 117 countries studied, and their efficiency is not very sensitive to targeting errors.